Suitability assessment for pluvial flood mitigation in dense urban areas, using nature-based solutions: a case of Delhi - Manish M. NAIR; Shama PARWEEN; Rajan Chandra SINHA (Journal of Urban and Regional Analysis)
Over the past years, pluvial floods have become a major concern for Indian cities. The factors that exacerbate the flood conditions include climate change, urbanisation, outdated stormwater infrastructure, decreasing capacity of natural wetlands, and natural stormwater sinks. As India's metropolitan cities are at risk due to their high rate of urbanisation, the study aims to develop a methodology to identify areas at risk due to pluvial floods, at a watershed scale. Also, it aims to support flood mitigation through nature-based solutions (NBS) and geospatial analysis, by considering the case of Delhi. Based on local flood data, the settlements at risk of pluvial floods were mapped using GIS, and the “pluvial flood susceptibility map” has been developed to assess the risk of flooding, followed by the selection of the most vulnerable local action area with the help of parameters like susceptibility (based on past pluvial flooding incidences) and urbanisation. Further, the “NBS suitability map” for the milli watershed (area of about 1000 to 10,000 ha) has been generated using the geospatial overlay technique of GIS. It can help identify potential areas within the study region at a sub-watershed level where NBS can be integrated, considering suitable and unsuitable conditions, based on physical, environmental, and planning parameters.